A preliminary study on the composition and distribution on marine macroflora along the intertidal zone of Piagao Island, Guimaras. - Gustilo, Rowena
This study was conducted primarily to determine the composition and distribution of marine macroflora along the intertidal zone of Piagao, Island, Guimaras. The Saito-Atobe method was used in the determination of the cover and frequency of the marine plants found in 84 quadrats for the four transect lines. A total of twenty seven species was found to be present in the study area. Of these twenty-seven species, six were composed of seagrasses and twenty-one were macrobenthic algae, of whic nine were represented by brown algae, eight were green algae, and four were red algae., The area was predominated by seagrass Enhalus acoroides. Dominance value of the area was found to be equal to 0.1711 while the diversity value was 0.9295. The high diversity value indicated that the area is highly stable and favorable for the growth of several organisms. Of all the environmental factors, the characteristics of the substratum played the most vital role in determining the distribution of marine macrobenthic plants in Piagao Cove.